Basic livestock nutrition [ - Pond, K. R.; Davis, G. W.; Maddox, Bill (CEV Multimedia, 2000)
This video presents information to understand the key topics associated with livestock nutrition; to gain an understanding of nutrition and what it comprises; to have a fundamental understanding of nutrients; and to understand how and why feed is processed